Study of maternal and perinatal outcome in cases of a HELLP syndrome - Kundaikar, Suharsha Laxmikant; Thakur, Ruchi Nityanand (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2023)
Background: HELLP is an acronym which describes the presence of haemolysis, elevated liver enzymes, low platelet count during pregnancy. It is a life-threatening manifestation of pre-eclampsia. The incidence of HELLP syndrome is 0.5-0.9% of all pregnancies and 10-20% in cases of pre-eclampsia. The rationale of this study lied in the anticipation that knowledge of incidence of the HELLP Syndrome will incite the interest of medical fraternity handling various pregnancy related complication. The results may also imply that early detection of high-risk individuals by primary medical personnel and timely referral to a tertiary care centre will be helpful in improving maternal and perinatal outcomes. Aim of this study were to study the incidence of HELLP syndrome in patients with pre-eclampsia and to study maternal and perinatal outcome in pre-eclampsia patients complicated with HELLP syndrome. Methods: A prospective observational study of 400 admitted cases with more than 20 weeks of gestation having pre-eclampsia. Statistical analysis of the data done on IBM SPSS Statistics Version. Results: The incidence of HELLP syndrome in pre-eclampsia was found to be 9.25%. The major maternal complications were placental abruption (35.14%), acute renal failure (16.22%), eclampsia (5.4%), papilledema (5.41%), PRES (5.41%), DIC (5.41%), maternal mortality (8.11%) in cases of HELLP syndrome while low birth weight (48.64%) respiratory distress syndrome (35.14%), meconium aspiration syndrome (18.9%), IUD (10.81%), NICU admission (37.84%), NND (10.81%) were neonatal complications. Conclusions: HELLP syndrome in pre-eclampsia is associated with significant maternal and perinatal morbidity and mortality and early detection and prompt management is the key for a better maternal and perinatal outcome.